499 AT1636, a colon cancer survivor-derived antibody recognizes a previously unidentified truncated, O-mannosylated 70kDa variant of E-cadherin. (9th November 2020) - Beaumont, Tim; Kedde, Martijn; Merat, Sabrina; Kwakkenbos, Mark; Bartels, Lina; Berg, Dorien van der; Wagner, Koen; Bakker, Arjen; Maijoor, Kelly; Bohne, Martino; Bru, Camille; Kattler, Veronika; et al.
Abstract : Background: Colorectal cancer (CRC) associated with Lynch syndrome is characterized by an abundance of infiltrating lymphocytes. To study whether tumor-specific antibodies with therapeutic potential can be isolated from these patients, the B-cell repertoire from a patient with Lynch syndrome who recovered from a stage IV colon carcinoma was screened. Here we describe an antibody, AT1636 that recognizes a previously unidentified O-mannosylated 70kDa form of E-cadherin. The intercellular interactions by E-cadherin on tumor cells have for long been recognized as protective in cancer metastasis, and deregulation of E-cadherin is a hallmark for epithelial-mesenchymal transition (EMT). Methods: The study protocol was approved by the Medical Ethical Committee of the Academic Medical Centre, Amsterdam, The Netherlands (NL42718.018.12). AIMM's BCL6 and Bcl-xL immortalization method 1 was used to interrogate the human antibody repertoire. From a carrier of a pathogenic gene variant in the MSH6 gene diagnosed with stage IV CRC and liver metastasis that had been treated with avastin, capecitabine and oxaliplatin, peripheral-blood memory B cells were obtained 9 years after last treatment. Antibodies-containing supernatant of cultured B-cells were screened for binding to 3 different CRC cell lines (DLD1, LS174T and COLO205) and absence of binding to fibroblast by flow cytometry. A high-affinity variant of AT1636 (AT1636IYN) was sorted from the original AT1636, AID-expressing B-cell clone. 2 Results: Antibodies that demonstrated differential binding to CRC cells were characterized and targets recognized by such antibodies were identified using immunoprecipitation and mass-spectrometry. One of the antibodies, AT1636, recognized a previously unidentified O-mannosylated 70kDa E-cadherin variant (ECV). Although the 70kDa ECV is found in all full-length E-cadherin expressing cells, tumor-specific binding of AT1636 is dependent on the O-mannosylation pattern in the antibody epitope on ECV. Using shRNA knock-down AT1636 binding was shown to depend on the transmembrane O-mannosyltransferase targeting cadherins 3 (TMTC3). 3 In accordance, coexpression of TMTC3 and E-cadherin in tumor cells is predictive for AT1636 binding. In addition, we observed that (over)expression of ECV results in a strong de-adhesive, EMT-like phenotype. Although AT1636 by itself is not able to induce ADCC, the CD3-bispecific antibody (single-chain UCHT1) AT1636 format specifically killed CRC cell lines. Conclusions: The AT1636 antibody retrieved from a patient with Lynch syndrome binds a previous unidentified cancer-specific O-mannosylated 70kDa form of E-cadherin. This variant might play a role in tumor-cell invasion and metastasis. More importantly, we provide a rationale to advance AT1636 based therapeutics for treatment of CRC. Ethics Approval: The study protocol was approved by the Medical Ethical Committee of the Academic Medical Centre, Amsterdam, The Netherlands (NL42718.018.12) References: M.J. Kwakkenbos, et al. Generation of stable monoclonal antibody-producing B cell receptor-positive human memory B cells by genetic programming. Nature Medicine 2010;16 :123–128. K. Wagner, et al. Bispecific antibody generated with sortase and click chemistry has broad antiinfluenza virus activity. Proc Natl Acad Sci USA 2014; 111: 16820–16825. I.S.B. Larsen, et al. Discovery of an O-mannosylation pathway selectively serving cadherins and protocadherins. Proc Natl Acad Sci USA 2017;114 :11163–11168.